Promising Techniques of Automotive Engine Lubrication Oil Monitoring System – A Critical Review towards Enhancement - Sivarao, Subramonian; Abdul Rahim , Samsudin; Haeryip , Sihombing; Taufik; Yuhazri, Yaakob; Sivakumar, Dhar Malingam; Tan, CheeFai (2012)
Engine lubricant plays a significant role in reducing internal friction between the piston and shear of moving mechanical parts to further improve the engine performance and efficiency. Rapid developments of engine oil monitoring systems has taken place to determine the engine lubricant degradation level in reducing unnecessary engine power loss and maintenance cost. This paper critically reviews the invention and an innovation pertaining to the subject before a smart innovation is developed in near future.